2015
DOI: 10.1002/hed.24302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elective neck dissection on the outcome of oral squamous cell carcinomas arising in the maxillary alveolus and hard palate

Abstract: Background Whether elective lymph neck dissection (ELND) is associated with improved survival in oral squamous cell carcinomas (SCC) of the maxillary alveolus/hard palate is not known. Methods One hundred ninety-nine patients presenting de novo and receiving treatment for clinically node negative SCC of the maxillary alveolus/hard palate at 2 cancer centers between 1985 and 2011 were analyzed. Results Forty-two patients (21%) received ELND. Occult nodal metastases were present in 29% of the dissected necks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Our study was able to critically examine the true epidemiology and prognosticators of SCCHP, which was not previously possible. Although prior studies describe an age range of 24 to 98 years, our cohort revealed an average age of 69.8 years with a slight female predominance. The finding of a female majority was similarly described in four separate studies involving SCCHP .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Our study was able to critically examine the true epidemiology and prognosticators of SCCHP, which was not previously possible. Although prior studies describe an age range of 24 to 98 years, our cohort revealed an average age of 69.8 years with a slight female predominance. The finding of a female majority was similarly described in four separate studies involving SCCHP .…”
Section: Discussionmentioning
confidence: 55%
“…Although prior studies describe an age range of 24 to 98 years, our cohort revealed an average age of 69.8 years with a slight female predominance. The finding of a female majority was similarly described in four separate studies involving SCCHP . The association of females affected more frequently with SCCHP is unclear; additional studies are needed to evaluate the significance.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In conformity within both studies, there is a preponderance of delayed metastasis for watchand-wait approach compared to END, with 13% (9/70) versus 5% (6/123) [11] and 74% (108/146) versus 31% (25/ 81), respectively [10]. Additionally, there is prospectively collected data from the 1980s and 1990s addressing the prevalence of clinical N-stage and survival outcome [12][13][14][15]. However, through changes in the demographic build-up of patient cohorts [16], precise radiological imaging for staging [17] as well as the introduction of optional chemotherapy additionally to the conventional adjuvant radiation therapy [18], these data are limited in explanatory value.…”
Section: Discussionmentioning
confidence: 69%
“…This suggests that adjuvant treatment of the lymph nodes, although not performed systematically, is warranted for patients with carcinoma of the maxilla classified as N0 by clinical or radiological assessment. Thus, a recent study by Givi et al [28] concluded that performing systematic elective neck dissection in clinically N0 patients revealed a high rate of occult node metastases (29%) and was associated with lower rate recurrences and improved survival.…”
Section: Discussionmentioning
confidence: 99%